Teaching Taoism in the 1990s - Kirkland, Russell (Teaching theology and religion, 1998)
To help non-specialists ensure that their teaching of Taoism is state-of-the-art, the author offers six suggestions: (1) Teach real Chinese Taoism, as it has been revealed by the social, textual, and historical research of Asian and Western specialists since the 1970s. (2) Use textbooks that reflect current scholarship. (3) Cover all phases of the Taoist tradition, not just the long-fetishized Lao-tzu and Chuang-tzu. The classical text entitled Nei-yeh helps students understand modern forms of Taoist meditation, such as those in Ch’üan-chen Taoism, which has been neglected in our textbooks. (4) Use reliable translations by responsible scholars. (5) Use real Taoist texts, such as now appear in Livia Kohn’s anthology, The Taoist Experience, and other new sourcebooks. (6) Make responsible choices. The author compares different pedagogical models and explains his own approach, designed to provide accurate knowledge of Taoist history and practices in a form that students will appreciate.